"There and Back Again": Going to Fantasy Lands to Learn How to Cope. Issue 1 (3rd July 2022) - Dewan, Pauline
ABSTRACT: The topic of children's mental health is appearing with increasing frequency in the media. Although some mental health problems require professional help, many children need assistance coping with day-to-day challenges. Children's fiction – a traditional source of support for managing life's difficulties – relies on the same principles as cognitive behavioral therapy and can help children by encouraging them to reframe unhelpful thoughts. Although fantasy novels may not be the first genre that teachers, librarians, parents, and childcare specialists think of in terms of bibliotherapeutic support, such novels can be particularly useful in helping children reformulate their thinking about problems.